2017
DOI: 10.1074/jbc.m116.762849
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Versatile Fluorogenic Transmembrane Peptide Substrates for Rhomboid Intramembrane Proteases

Abstract: Rhomboid proteases are increasingly being explored as potential drug targets, but their potent and specific inhibitors are not available, and strategies for inhibitor development are hampered by the lack of widely usable and easily modifiable activity assays. Here we address this bottleneck and report on the development of new fluorogenic transmembrane peptide substrates, which are cleaved by several unrelated rhomboid proteases, can be used both in detergent micelles and in liposomes, and contain red-shifted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 36 publications
3
49
0
Order By: Relevance
“…As the DDM concentration exceeded 0.5%, the apparent enzyme activity decreased and is presumably due to an increase in empty micelles and the relative decrease in accessible substrate. Our results are well correlated with a previous study on a transmembrane rhomboid protease that showed similar trends in activity with increases in DDM . In fact, in agreement with Tichá et al ., the slope of the Log–Log plot at high DDM concentration (Fig.…”
Section: Resultssupporting
confidence: 93%
“…As the DDM concentration exceeded 0.5%, the apparent enzyme activity decreased and is presumably due to an increase in empty micelles and the relative decrease in accessible substrate. Our results are well correlated with a previous study on a transmembrane rhomboid protease that showed similar trends in activity with increases in DDM . In fact, in agreement with Tichá et al ., the slope of the Log–Log plot at high DDM concentration (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Bacillus subtilis genome encodes two rhomboid protease genes, ydcA and yqgP [also known as gluP (Mesak et al , )]. No proteolytic activity has been detected for YdcA so far (Urban et al , ; Lemberg et al , ), while YqgP is a commonly used model rhomboid protease cleaving a number of synthetic substrates (Lemberg et al , ; Urban & Wolfe, ; Ticha et al , ,b). YqgP has homologs in a number of Gram‐positive bacteria, including Bacilli, but also Staphylococci, Listeriae and others (http://www.ebi.ac.uk/interpro/protein/P54493/similar-proteins), and thus represents an attractive system to explore the cell biology and functions of bacterial rhomboid proteases.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously structural analysis of the RseP–substrate complex will be needed to understand the molecular details of the interaction between RseP and a substrate. In addition, kinetic analysis using purified RseP and substrates in solubilized and reconstituted systems as conducted for other I‐CLiPs (Strisovsky et al ., ; Dickey et al ., ; Kamp et al ., ; Bolduc et al ., , Tichá et al ., ) will be useful for functional characterization of the two substrate‐binding sites. Such analyses would provide an important basis to elucidate the mechanisms underlying specific substrate recognition and cleavage by RseP and other S2P proteases.…”
Section: Discussionmentioning
confidence: 99%